Improving high rate cycling limitations of thick sintered battery electrodes by mitigating molecular transport limitations through modifying electrode microstructure and electrolyte conductivity. Issue 9 (30th July 2021) - Nie, Ziyang; Parai, Rohan; Cai, Chen; Ghosh, Dipankar; Koenig, Gary M.
Abstract : Mitigating molecular transport limitations in thick sintered battery electrodes with electrolyte and microstructure design. Abstract : For batteries, thicker electrodes increase energy density, however, molecular transport limits the rate of charge/discharge for extracting large fractions of available energy. Mitigating transport limitations by increasing electrolyte conductivity and aligning the pores in the electrode microstructure are described.